Economic and microbiological evaluation of towels and cloths used during milking - Varela-Vargas, María José (2021)
Introduction. The practices before milking help promote healthy udders and the productivity of the animals. Objective. To realize an economic and microbiologic comparison of the use of  cloths and towels during the teats disinfection. Materials and methods. This research was carried out in Tilaran, Guanacaste, Costa Rica between October and November 2018, in a production system that performs three milkings every 8 h and keeps its animals in complete stabling. A random five towels to dry the teats before milking were taken, which were washed and reused in the next milking. The towels were cut in half, both sides were identified, the relationship between them was maintained, one part was stored in an airtight bag (used towel), and the other one was washed, and its reuse was simulated. After being washed, both parts (ten cloths) were analyzed to quantify the population of Escherichia coli, Staphylococcus aureus, and aerobes. For the economic analysis, the number of towels used per animal, the shelf life, the number of times used, the cost of each towel, water, electricity, chlorine, and liquid detergent were recorded. Results. The washing cycle used decreased 800 times of the population of Escherichia coli, by 5000 times the aerobes, and 500 times the Staphylococcus aureus. The paper towels analyzed had UFC g-1 lower than ten at the time of use. There is a similarity between the use of two towels/animal/milking with microfiber towels, and it rules out the use of three towels/animal/milking because it increases the cost by 48.59 %. Conclusion. There were no economic or microbial differences between the microfiber towels and the two paper towels used to dry the teats during the pre-selling.